An enumerative coding technique for DC-free runlength-limited sequences - Braun, V.; Schouhamer immink, K.A. (IEEE transactions on communications, 2000)
We present an enumerative technique for encoding and decoding DC-free runlength-limited sequences. This technique enables the encoding and decoding of sequences approaching the maxentropic performance bounds very closely in terms of the code rate and low-frequency suppression capability. Use of finite-precision floating-point notation to express the weight coefficients results in channel encoders and decoders of moderate complexity. For channel constraints of practical interest, the hardware required for implementing such a quasi-maxentropic coding scheme consists mainly of a ROM of at most 5 kB.